2020
DOI: 10.3892/ol.2020.11527
|View full text |Cite
|
Sign up to set email alerts
|

NGAL protects in nasopharyngeal carcinoma by inducing apoptosis and blocking epithelial‑mesenchymal transition

Abstract: In recent years, neutrophil gelatinase-associated lipocalin (NGAL) has been considered to be a key molecule in different cancer types and its carcinogenesis may be related to the NGAL/MMP-9 complex. However, its expression pattern and role in nasopharyngeal carcinoma (NPC) has rarely been reported. In the current study, 158 tumor tissues from NPC patients were collected and immunohistochemistry was performed to determine the NGAL protein expression, to investigate the correlation between its expression and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 44 publications
0
8
1
Order By: Relevance
“…Moreover, NGAL is a type of injury-induced transferrin that may improve the activation of intracellular coenzyme iron and regulate various important proteins involved in cellular activities ( 19 ). For example, Guo et al ( 20 ) revealed that NGAL modulates cell apoptosis and epithelial-mesenchymal transition in nasopharyngeal carcinoma. Han et al ( 21 ) demonstrated that NGAL participates in LPS-mediated apoptosis of renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NGAL is a type of injury-induced transferrin that may improve the activation of intracellular coenzyme iron and regulate various important proteins involved in cellular activities ( 19 ). For example, Guo et al ( 20 ) revealed that NGAL modulates cell apoptosis and epithelial-mesenchymal transition in nasopharyngeal carcinoma. Han et al ( 21 ) demonstrated that NGAL participates in LPS-mediated apoptosis of renal tubular epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…NGAL is synthesised during a narrow window of granulocyte maturation in the bone marrow but also may be induced in epithelial cells in the setting of inflammation or malignancy [ 51 , 52 ]. The gene for this protein is located on chromosome 9 [ 53 ].…”
Section: Biomarkers Of Allogeneic Kidney Transplant Rejectionmentioning
confidence: 99%
“…Previous studies have reported that LCN2 is involved in pathological disorders, especially in inflammation, metabolic disease, neurological disease, and cancers. Recently, an immunohistochemical analysis of NPC tumor specimens demonstrated that LCN2 expression is associated with the survival of NPC patients [ 9 , 10 ]. A high expression of LCN2 has been found to be positively associated with improved 5-year overall survival in NPC patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an immunohistochemical analysis of NPC tumor specimens demonstrated that LCN2 expression is associated with the survival of NPC patients [ 9 , 10 ]. A high expression of LCN2 has been found to be positively associated with improved 5-year overall survival in NPC patients [ 10 ]. Conversely, a recent study showed that a high expression of LCN2 is associated with a poor 5-year relapse-free survival and local relapse-free survival, but not with distant metastasis-free survival, progression-free survival and overall survival between high- and low-LCN2-expression groups in NPC patients [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation